Oligonucleotide fingerprinting detects genetic variability at different levels in Nigerian Mycosphaerella fijiensis - Muller, R.; Pasberg-Gauhl, C.; Gauhl, F.; Ramser, J.; Kahl, G. (Wiley, 1997)
DNA fingerprinting with synthetic simple repetitive oligonucleotides such as (CA)8 or (CAA)5 detected polymorphisms between various isolates of the ascomycete Mycosphaerella fijiensis, the causal agent of the black Sigatoka disease of Musa. These microsatellite motifs are present at multiple chromosomal locations and in high copy numbers in the Mycosphaerella genome, generating informative fingerprints with low background. Variability exists on a macro‐ as well as a microgeographical scale: it occurred within one lesion, between lesions of one plant, between plants, cultivars, and geographic locations. Mathematical analysis of the data produced dendrograms that demonstrated the presence of different genetically related groups of Mycosphaerella fijiensis in Nigeria.